Distress tolerance, anxiety-related symptoms, stress, and depression among dropout and non-dropout university students: a mediation analysis - Qasir Abbas; Latif, Iqra; Muneer, Mehwish; Khan, Muhammad Umar; Baig, Khawer Bilal (Journal of the Pakistan Medical Association, 2023)
This study explores the relationship between distress tolerance and depression with mediating role of anxiety-related symptoms and stress among dropout and non-dropout university students. This cross-sectional study was conducted from October 2019 to December 2020. Participants’ age ranged between 20-40 years. Data was collected using the Distress Tolerance Scale and Depression Anxiety and Stress Scale. Descriptive, t-test, and mediation analyses were performed to calculate the results. A sample of 500 respondents was recruited. A significant difference was noted between dropout and non-dropout students on CGPA (p<.001), depression (p<.001), anxiety (p<.001), stress (p<.001), tolerance (p<.001), absorption (p<.001), appraisal (p<.001), and distress tolerance (p<.001). Mediation analysis reveals that stress and anxiety significantly mediates between distress tolerance and depressive symptoms (i.e., F (498) = 31.14, p< .001; F (498) =34.14, p< .001; F (496) = 161.21, p< .001). It is concluded that low distress tolerance increases stress and anxiety, triggering depressive symptoms.